The Quality of Life on Asthmatic Adolescent and Its Correlation with the Severity and Control of Asthma - Lisa Adhia Garina; Muhammad Ridho Grahadinta; Ferry Achmad Firdaus Mansoer; Intan Puspitasari (Global Medical & Health Communication (GMHC), 2020)
Asthma is considered a global health problem that, if not managed properly, can reduce the sufferers' quality of life. The purpose of the study was to evaluate the quality of life from the perspectives of asthma severity and the asthma control level. A cross-sectional study was conducted from February to June 2018 on asthmatic adolescents aged 12–14 years old in two public junior high schools in Bandung city, Indonesia. The diagnosis, history of asthma,  severity, and asthma control were established based on the National Asthma Guidelines from the Indonesian Pediatric Society, Global Initiative for Asthma (GINA), asthma control test (ACT), and ISAAC questionnaire. Statistical analysis performed using SPSS v.20 with Spearman's rho to determine the significance. The gender distribution of the 98 subjects was almost similar with slightly more girls (51%). The median age was 13±1 years with average ACT, FVC, and PAQLQ(S) total scores of 20±4, 78±16%, and 5.3±1.3, respectively. The domain scores for symptoms, activity limitations, and emotional function were 4.9±1.4, 5.0±1.3, and 5.7±1.1, respectively. There are correlations between the total  PAQLQ(S) score and asthma severity (p<0.001, r=−0.5) and the level of asthma control (p<0.001, r=0.6). In summary, the quality of life has a relationship with asthma severity and the level of asthma control. Asthma management should not only focus on medication but also ways to maintain a good quality of life. KUALITAS HIDUP REMAJA ASMA DAN HUBUNGANNYA DENGAN KEKERAPAN GEJALA DAN DERAJAT KENDALI ASMAAsma masih menjadi masalah kesehatan penting yang jika tidak ditangani baik, asma dapat menurunkan kualitas hidup anak. Tujuan penelitian ini menilai kualitas hidup dan hubungannya dengan kekerapan gejala dan derajat kendali asma. Penelitian cross-sectional ini dilaksanakan dari bulan Februari hingga Juni 2018 pada remaja asma berusia 12–14 tahun di dua SMPN di Kota Bandung, Indonesia. Diagnosis, riwayat asma, kekerapan gejala, dan derajat kendali asma berdasar atas Pedoman Nasional Asma Anak Ikatan Dokter Anak Indonesia, Global Initiative for Asthma (GINA), asthma control test (ACT), dan kuesioner dari ISAAC. Analisis statistik menggunakan SPSS v.20 dengan uji Spearman’s rho untuk menentukan signifikansi. Distribusi gender dari 98 subjek penelitian hampir sama dengan sedikit lebih banyak perempuan (51%). Usia rerata subjek 13±1 tahun dengan skor rerata ACT, FVC, PAQLQ(S) masing-masing 20±4, 78±16%, dan 5,3±1,3. Skor domain gejala, keterbatasan beraktivitas, dan fungsi emosi masing-masing 4,9±1,4; 5,0±1,3; dan 5,7±1,1. Terdapat hubungan skor total PAQLQ(S) dengan kekerapan gejala (p<0,001; r=−0,5) dan dengan derajat kendali asma (p<0,001; r=0,6). Simpulan, kualitas hidup berhubungan dengan kekerapan gejala dan derajat kendali asma. Pengelolaan asma sebaiknya tidak hanya memperhatikan pengobatan, tetapi juga menjaga kualitas hidup yang baik.